Improving teacher performance through motivation: the role of academic supervision and principal leadership - Hendrajaya Hendrajaya; Dewi Setiyowati; Andhi Supriyadi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This research is located in junior high schools Kendal Regency, with purpose of the research being to analyze and understanding the influence of Academic Supervision and Principal Leadership on Work Motivation, Academic Supervision, Principal leadership and work motivation on teacher performance, (Academic Supervision on teacher performance mediated by work motivation, and Principal leadership towards performance mediated work motivation. This study used a sample of 118 people who were state civil service teachers at SMPN in Kendal Regency Data collection methods using questionnaires and interviews, from the results of questionnaire answers in feasibility tests using validity tests and reliability tests, as well as analyzing data using regression analysis, model tests and hypothesis test. Results of this research concluded that: Academic Supervision and Principal Leadership affects Work Motivation, Academic Supervision, Principal Leadership and Work Motivation affects teacher performance, Academic Supervision influences teacher performance mediated by work motivation, and the influence of Principal Leadership on teacher performance Mediated Work Motivation.